Passive house design aspects and analysis in Lithuania - Adomaitis, Rimvydas; Valančius, Kęstutis (International Conference “Environmental Engineering”, 2023)
The article provides an analysis of the environment for the development of energy-efficient single-family dwellings in Lithuania in the context of European Union (EU) requirements, Lithuanian (LT) regulations, and climate change trends. It examines the role of Lithuanian architects and builders and the arsenal of tools and challenges in developing energy-efficient houses. The principles and best practices of the German Passive House Institute for Passive House development, their application in Lithuanian climate conditions, specific Passive Houses built in Lithuania, and their operational results are analyzed. The relevance of monitoring in validating the digital building model’s energy efficiency and comfort results as a critical tool for energy-efficient design and of the built houses from assessed. This paper aims to review the regulatory environment for architects working on energy-efficient homes and identify the main objective factors that make this process difficult in Lithuania. In this article we also aimed to provide an overview of the Passive House certification system as a third-party certification system for energy efficient buildings, its evolution, and the place of Passive House in the context of energy efficient buildings in Lithuania. The study shows that although the situation is improving, several obstacles have a significant impact on holding back the process of developing energy-efficient homes, and their solution requires systematic work and much time, which creates a reasonable risk of not meeting the EU and LT energy efficiency targets for buildings in time. We can also see that Passive Houses, built more than a decade ago, are still topping the list of energy-efficient houses in Lithuania today, thanks to their uncompromising rating system.